2014
DOI: 10.5539/gjhs.v6n4p107
|View full text |Cite
|
Sign up to set email alerts
|

Pabon Lasso and Data Envelopment Analysis: A Complementary Approach to Hospital Performance Measurement

Abstract: Background:Performance measurement is essential to the management of health care organizations to which efficiency is per se a vital indicator. Present study accordingly aims to measure the efficiency of hospitals employing two distinct methods.Methods:Data Envelopment Analysis and Pabon Lasso Model were jointly applied to calculate the efficiency of all general hospitals located in Iranian Eastern Azerbijan Province. Data was collected using hospitals’ monthly performance forms and analyzed and displayed by M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 15 publications
3
35
1
6
Order By: Relevance
“…In addition, using the Pabón‐Lasso model, we identified only a few facilities in the high utilisation sector. Similarly, previous studies showed that around 20% to 45% of facilities appear in the high‐performance sector (III) . These results indicate excess bed capacity in health facilities given the current level of utilisation.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In addition, using the Pabón‐Lasso model, we identified only a few facilities in the high utilisation sector. Similarly, previous studies showed that around 20% to 45% of facilities appear in the high‐performance sector (III) . These results indicate excess bed capacity in health facilities given the current level of utilisation.…”
Section: Discussionsupporting
confidence: 74%
“…Similarly, previous studies showed that around 20% to 45% of facilities appear in the high-performance sector (III). 27,[48][49][50] These results indicate excess bed capacity in health facilities given the current level of utilisation.…”
Section: Utilisationmentioning
confidence: 99%
“…Regarding the implementation of the HSRP in all hospitals affiliated to the ministry of health since May 2014, some selected performance indicators were examined in the concerned hospitals. In order to evaluate the performance of the hospital, several indicators are used, among which the bed occupancy rate (BOR), bed turnover rate (BTR), and average length of stay (ALS) are the most important and most often-used indicators for assessing the hospital efficacy and have been used in well-known hospital performance measurement models such as Pabon and Lasso's (25,26).…”
Section: Methodsmentioning
confidence: 99%
“…All other things being equal, a shorter stay will reduce the cost per discharge and shift care from inpatient to less expensive post-acute settings. The ALOS refers to the average number of days that patients spend in the hospital (25).…”
Section: Methodsmentioning
confidence: 99%
“…They are also the starting point of human development (5). Therefore, efficiency is the most important and the commonest mechanism to evaluate and measure the performance of enterprises like hospitals (6). There are numerous indicators that allow the evaluation of the productivity or lack of productivity of a hospital.…”
Section: Introductionmentioning
confidence: 99%